EFEK BALANCE SCORECARD TERHADAP PENENTUAN STRATEGI PERUSAHAAN - Lila Retnani Utami (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
the creative industry is a business activity that focuses on creativity and innovation. Creative industries based on creativity and innovation will grow if supported by adequate technology. New Wave era marked by the rapid progress in the field of Technology and Communications strongly supports the development of creative industries. Performance measurement of the company has been mostly only seen from the financial side, but there are still more assets of the company to the intangible assets. Based on the development of the current industrial world and the existence of intangible assets of corporate assets, the company's performance is not enough if only measured from the financial side, the company's performance should also need to assess the non-financial side. The purpose of this paper is to assess the performance of the company from the financial and non-financial side. The type of this research is quantitative descriptive, using business object with name BUCINI LEATHER CRAFT Yogyakarta, Data used in the form of obtained from interview and secondary data in the form of financial statement data of last 3 years and literature study. Analyzer to measure company performance by using balance scorcard, Balance scorcard is a measure of management to assess performance or health from side of finance and non finance. Assessment of balance scorecard in addition to financial aspects as well as aspects of customer satisfaction, internal business process aspects, aspects of learning and growth. Management achievement can also be determined by using this tool, but it can also be used to make improvements towards the achievement of the company's vision and mission. The expected result is expected to obtain a description of the company's strategy to achieve optimal profit both in financial and non-financial terms. Keywords: Balance Scorecard, performance, creative industry